Depression and its treatment - Pollitt, John D. (Heinemann monograph, 1965)
Depression and its Treatment focuses on medical interventions in the diagnosis and treatment of depression, as well as identification of symptoms and possible mechanisms of treatment. The book first offers information on the concept and classification of depression, physiology and psychopathology, and clinical types of depression, including classification of depressive illnesses and etiology. The publication then takes a look at the treatment of psychological and physiological depression and complications of depression and their treatment. The text ponders on the prognosis of psychological an.